Dynamic, transient, and robust increase in the innervation of the inflamed mucosa in inflammatory bowel diseases - Gonzalez Acera, Miguel; Bubeck, Marvin; Mascia, Fabrizio; Diemand, Leonard; Sturm, Gregor; Kuehl, Anja A.; Atreya, Raja; Lie, Dieter Chichung; Neurath, Markus; Schumann, Michael; Klose, Christoph S. N.; Trajanoski, Zlatko; et al. (Cells, 2021)
Inflammatory bowel diseases (IBD) are characterized by chronic dysregulation of immune homeostasis, epithelial demise, immune cell activation, and microbial translocation. Each of these processes leads to proinflammatory changes via the release of cytokines, damage-associated molecular patterns (DAMPs), and pathogen-associated molecular patterns (PAMPs), respectively. The impact of these noxious agents on the survival and function of the enteric nervous system (ENS) is poorly understood. Here, we show that in contrast to an expected decrease, experimental as well as clinical colitis causes an increase in the transcript levels of enteric neuronal and glial genes. Immunostaining revealed an elevated neuronal innervation of the inflamed regions of the gut mucosa. The increase was seen in models with overt damage to epithelial cells and models of T cell-induced colitis. Transcriptomic data from treatment naïve pediatric IBD patients also confirmed the increase in the neuroglial genes and were replicated on an independent adult IBD dataset. This induction in the neuroglial genes was transient as levels returned to normal upon the induction of remission in both mouse models as well as colitis patients. Our data highlight the dynamic and robust nature of the enteric nervous system in colitis and open novel questions on its regulation.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Crohn’s disease; Enteric nervous system; Inflammatory bowel diseases; Neurogenesis; Ulcerative colitis